2016
DOI: 10.1016/j.imr.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in skeletal muscle mitochondria: the role of exercise

Abstract: Aging is associated with mitochondrial dysfunction, which leads to a decline in cellular function and the development of age-related diseases. Reduced skeletal muscle mass with aging appears to promote a decrease in mitochondrial quality and quantity. Moreover, mitochondrial dysfunction adversely affects the quality and quantity of skeletal muscle. During aging, physical exercise can cause beneficial adaptations to cellular energy metabolism in skeletal muscle, including alterations to mitochondrial content, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 41 publications
2
37
1
3
Order By: Relevance
“…For example, attenuation of muscle regeneration in satellite cells from old mice was shown to decrease when aged satellite cells were paired to young circulatory environments, indicating that repair can be influenced by the local cellular environment. Several studies have suggested that excess ROS generated from mitochondrial respiration can damage cellular structures and may contribute to cellular aging . It is possible, although speculative, that skeletal muscle containing high levels of SIRT1 may release more mitochondrial‐associated ROS than SIRT1 knockout models during injury and repair and thereby impair the proliferation capacity in satellite cells during muscle repair.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attenuation of muscle regeneration in satellite cells from old mice was shown to decrease when aged satellite cells were paired to young circulatory environments, indicating that repair can be influenced by the local cellular environment. Several studies have suggested that excess ROS generated from mitochondrial respiration can damage cellular structures and may contribute to cellular aging . It is possible, although speculative, that skeletal muscle containing high levels of SIRT1 may release more mitochondrial‐associated ROS than SIRT1 knockout models during injury and repair and thereby impair the proliferation capacity in satellite cells during muscle repair.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and proper nutrition represent the best lifestyle measures to prevent and to retard age-related sarcopenia and progressive muscular weakness [115,116]. Remarkably, regular and controlled exercise with advancing age prolongs lifespan and improves skeletal muscle mass and performance [117,118].…”
Section: Exercise-an Anti-aging Strategy That Preserves Mitochondria mentioning
confidence: 99%
“…Mitochondria are dynamic organelles that regulate cellular functions such as cellular respiration, calcium homeostasis, and reactive oxygen species (ROS) production. The most important role of mitochondria is energy metabolism, which involves production of adenosine triphosphate (ATP) through oxidative phosphorylation in skeletal muscle mitochondria [ 10 ]. In addition, mitochondria have a morphological and structural cycle referred to as mitochondrial dynamics (fusion, fission, and mitophagy) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%